Transformation and outcome of nodular lymphocyte predominant Hodgkin lymphoma: a Finnish Nationwide population-based study - Kalashnikov Ilja; Tanskanen Tomas; Pitkaniemi Janne; Malila Nea; Jyrkkio Sirkku; Leppa Sirpa (SPRINGERNATURE, 2022)
Nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is a rare B-cell malignancy associated with excellent survival. However, some patients experience histological transformation into aggressive large B-cell lymphoma. Population-based data on transformation in patients with NLPHL is limited. We conducted a nationwide population-based study to estimate the risk of transformation and relative survival in patients diagnosed with NLPHL in Finland between 1995 and 2018. We identified a total of 453 patients (median age, 48 years; 76% males) with the incident NLPHL from the Finnish Cancer Registry. The cumulative incidence of transformation was 6.3% (95% CI, 4.2-9.6) at 10 years. After adjusting for sex, age and year of diagnosis, transformation was associated with a substantially increased risk of death (HR 8.55, 95% CI 4.49-16.3). Ten-year relative survival was 94% (95% CI, 89%-100%). The patients diagnosed at a later calendar year had lower excess risk of death (HR, 0.38 per 10-year increase; 95% CI, 0.15-0.98). We conclude that while the 10-year relative survival for the patients with NLPHL was excellent in this large population-based cohort for the entire study period, transformation resulted in a substantially increased mortality compared with the patients without transformation. Our results also suggest a reduction in excess mortality over time.